Theoretical investigation of solvent effects on reactivity, spectroscopic properties, and inhibitory potential of a dihydropyridine derivative against Vibrio cholorae: DFT, molecular docking and pharmacokinetics evaluation - Israel A. Ekoro; Justina I. Mbonu; Christiana E. Ogwuche; Sabina C. Agu; Hamzah A. Bawa (Discover Chemistry)
Abstract The emergence of drug-resistant bacterial strains has made cholera an imminent threat to health. Addressing this challenge requires an exploration of new alternative medicines. In this work, density functional theory at B3LYP/6-311G (d, p) was employed to examine the effect of solvents on 4-(((cis)-4-aminocyclohexyl) amino)-N-(3-(methyl sulfonyl) phenyl)-2-oxo-1,2-dihydropyridine-3-carboxamide (AMDC) reactivity and spectral details. The reactivity of AMDC was shown to be solvent-dependent. The highest energy gap of 4.504 eV was found for AMDC in water, while other phases: Ethanol and gas phase had lesser energy gaps of 4.500 eV, 4.354 eV respectively showing degrees of stability and reactivity under different solvents. The suitability of AMDC as a potential Vibrio cholerae inhibitor was then evaluated using the ADMET parameters and results showed that AMDC fulfilled Lipinski’s rule and is therefore drug-like. Significant binding affinity scores were obtained from molecular docking studies against Vibrio cholera proteins (PDB ID: 3GBG and 6EHB), with 3GBG showing a stronger interaction (−9.4 kcal/mol). The observations from this research provided important information on AMDC’s reactivity and inhibiting potential, making it an option for more investigation in the hunt for efficient cholera treatments.